2023
DOI: 10.7759/cureus.35425
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Pulmonary Hypertension and Silicosis in a Bluestone Cutter: A Case Report on Raising Awareness

Abstract: This case report describes a patient who developed pneumoconiosis in the form of silicosis and group 1 pulmonary hypertension (PH) due to his unprotected work as a bluestone cutter. Bluestone is a type of sandstone used in outdoor construction commonly in the North-east region of the US. In the literature and to our knowledge, blue stone mining has not been viewed as a risk factor for pneumoconiosis. This case report aims to increase awareness about this occupational hazard. Additionally, it is known that chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A study showed that in patients 45 years and younger, the risk of acute respiratory failure was found to be 2.11 times greater than in patients aged 45-64 years and 9.11 times greater in those who were 65 years or older, showing that younger patients are more likely to develop this complication. The study also showed that polymyositis patients with comorbidities like hypertension, chronic obstructive pulmonary disease (COPD), and peripheral vascular disease are at higher risk of developing acute respiratory failure [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that in patients 45 years and younger, the risk of acute respiratory failure was found to be 2.11 times greater than in patients aged 45-64 years and 9.11 times greater in those who were 65 years or older, showing that younger patients are more likely to develop this complication. The study also showed that polymyositis patients with comorbidities like hypertension, chronic obstructive pulmonary disease (COPD), and peripheral vascular disease are at higher risk of developing acute respiratory failure [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%